THE IMPACT OF KOREAN DRAMAS ON TEENAGERS - Selfitrida A.yani; Silvina Mutia Afrianda (Jurnal Warta Dharmawangsa, 2023)
ABSTRACT- Korean drama is the result of the spread of Korean culture or commonly referred to as hallyu. Korean drama lovers themselves have viewers from all kinds of backgrounds, but generally from teenagers. This study aims to analyze what impact is generated from watching K-Drama, especially teenagers, will it have a positive or even negative impact. The method used in this research is descriptive quantitative method by describing the data that has been collected. The results of this journal review show that watching K-Drama will have an impact on the economic, socio-cultural, psychological and health fields for adolescents.Keywords : Korean Drama, Youth Education, Hallyu